Hukum istinbath dalam fatwa MUI - Riyandini, Ariyanti Septy (Maliki Interdisciplinary Journal, 2024)
Human knowledge is dynamic and continues to develop from time to time. Allah has endowed humans with rationality, which can be very useful for digesting many experiences, conducting research and reasoning. Human information is eager to be organized and managed to leverage real information to offer causes of informational excellence. Istinbath has a goal to set a law on every action. Meanwhile, a fatwa has the aim of answering questions regarding Sharia law for the benefit of society and the explanation can be delivered in oral or written form which is not binding. Indonesia has a Fatwa institution, one of which is the Indonesian Ulema Council (MUI). MUI uses the Al-Quran, Sunnah (Hadith), Ijma’ and Qiyas as the basis for establishing Fatwas. MUI stipulates 86 fatwas on Sharia finance and banking. Istinbath is an effort to find laws from the texts of the Al-Quran and Hadith which is done by devoting the ability of reason and thought. Ushul scholars from four schools of thought, namely Imam Abu Hanifah, Imam Maliki, Imam Syafi’i and Imam Hambali believe that the Al-Quran, Hadith and Ijma’ are the laws of istinbath.